Die Theorie des Guten in Aristoteles' Nikomachischer Ethik - Brüllmann, Philipp (Quellen und Studien zur Philosophie, 2011)
The series, founded in 1970, publishes works which either combine studies in the history of philosophy with a systematic approach or bring together systematic studies with reconstructions from the history of philosophy. Monographs are published in English as well as in German. The founding editors are Erhard Scheibe (editor until 1991), Günther Patzig (until 1999) and Wolfgang Wieland (until 2003). From 1990 to 2007, the series had been co-edited by Jürgen Mittelstraß.
Keywords: Hochschulschrift; Das Gute; Aristoteles / Ethica Nicomachea